The development approach of a pedagogically-driven serious game to support relationship and sex education (RSE) within a classroom setting. - Arnab, S.; Brown, K.; Clarke, S.; Dunwell, I.; Lim, T.; Suttie, N.; Louchart, S.; Hendrix, M.; de Freitas, Sara (Pergamon, 2013)
Didactic approaches to Relationships and Sex Education (RSE) have been shown to yield limited outcomes when compared to approaches that stimulate peer discussion and debate. Creating effective interventions, which stimulate peer involvement, remains a demanding task and finding a solution that is not only engaging but also pedagogically sound is vital. A case thus exists for exploring how game technology might facilitate more feasible solutions. This paper presents the development approach of a digital game: PR:EPARe (Positive Relationships: Eliminating Coercion and Pressure in Adolescent Relationships), designed by a cross-disciplinary team of UK researchers from Coventry University's Studies in Adolescent Sexual Health (SASH) research group and the Serious Games Institute (SGI). Psychological targets for game content were identified through Intervention Mapping (IM) and the game design process was based on the Four-Dimensional Framework of Learning (4DF) emphasizing the context of deployment, learner profiling and the pedagogical perspective that influence the mode of representation of the learning content. Early efficacy testing of the game solution was validated through a cluster-randomized controlled trial in local schools (n = 505) indicated some positive outcomes in favour of the game-based approach, based on self-reported measures of psycho-social preparedness for avoiding coercion (F [3, 501] = 15.306, p < .001, ?p2 = 0.084). Analysis of observation data suggests that blending this interactive game-based approach with traditional classroom delivery encouraged the teachers and students to engage in communal discussions and debriefing during and after game play. Together, the results demonstrated real benefits for pedagogy-driven game-based approaches to support the delivery of RSE within a classroom setting.